THE PARADIGM OF MERDEKA BELAJAR AND THE TEACHERS' DIGITAL COMPETENCE IN ERA 4.0 - Wijanarko, Heru (Antis-Publisher, 2024)
Education has undergone a significant transformation along with the development of technology. The technological development of Era 4.0 marks a change in the educational landscape, giving rise to the concept of